THE CONTRIBUTION OF SCHOLARS OF UZBEKISTAN TO THE SCIENTIFIC AND EDUCATIONAL STUDY OF SUFI TEACHINGS IN THE ERA OF GLOBALIZATION - Khatamov Tokhir Abdumutalovich (Sciental Journals Publishing, 2025)
This article highlights the research, lectures, works, and online activities of Shaykh Muhammad Sadiq Muhammad Yusuf focused on explaining the true essence of Sufi teachings.
Keywords: Shaykh Muhammad Sadiq Muhammad Yusuf, Sufism, tazkiyah (purification), spiritual upbringing, works, lectures, websites.